Place-based interpretation of the sustainable development goals for the land-river interface - Vercruysse, Kim; Grabowski, Robert C.; Holman, Ian P.; Azhoni, Adani; Bala, Brij; Meersmans, Jeroen; Peng, Jian; Shankar, Vijay; Mukate, Shrikant; Poddar, Arunava; Wang, Xiaoyu; Zhang, Zimo (Springer, 2022)
The land–river interface (LRI) is important for sustainable development. The environmental processes that define the LRI support the natural capital and ecosystem services that are linked directly to multiple Sustainable Development Goals (SDGs). However, existing approaches to scale up or down SDG targets and link them to natural capital are insufficient for the two-way human–environment interactions that exist in the LRI. Therefore, this study proposes a place-based approach to interpret the SDG framework to support sustainable land/water management, by (i) identifying key priorities for sustainable development through a normative content analysis of the SDG targets, and (ii) illustrating these priorities and associated challenges within the LRI, based on a literature review and case-studies on human–environment interactions. The content analysis identifies three overarching sustainable development priorities: (i) ensuring improved access to resources and services provided by the LRI, (ii) strengthening the resilience of the LRI to deal with social and natural shocks, and (iii) increasing resource efficiency. The review of the current state of LRIs across the world confirms that these are indeed priority areas for sustainable development. Yet, the challenges of attaining the sustainable development priorities in the LRI are also illustrated with three examples of development-related processes. Urbanisation, dam construction, and aggregate mining occur within specific zones of the LRI (land, land–river, river, respectively), but their impacts can compromise sustainable development across the entire LRI and beyond. The existence of these unintended impacts highlights the need to consider the geomorphic, hydrological, and ecological processes within the LRI and how they interact with human activity. Identifying the place-based priorities and challenges for sustainable development will help achieve the SDGs without compromising the functions and services of the LRI.
Keywords: Sustainable development priorities; Land–river interface; Human–environment interactions; Hydrology; Geomorphology; Ecology